2020
DOI: 10.1109/access.2020.3013031
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Impedances Optimization to Enhance Microgrid Small-Signal Stability and Reactive Power Sharing

Abstract: Microgrid instability poses critical issues to the power delivery following a load change or a tripping event. In island operating mode lack of grid intensifies this challenge. This study aims at controlling several converter-based distributed generations (DG) sharing the power in an island microgrid (MG). At first, the microgrid model including virtual impedances and phase-locked loop (PLL) is introduced. Afterwards a novel small-signal stability analysis for island microgrids is proposed. Finally, an optimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 37 publications
0
34
0
Order By: Relevance
“…The virtual impedance optimization in [19] has minimized the reactive power mismatches among converters and enhanced the microgrid small-signal stability by an off-line PSO algorithm. Following the analysis of microgrid stability domain in [20], it has been suggested that the proportionalderivative reactive power controller enhances the microgrid stability margin.…”
Section: Nomenclature Abbreviationsmentioning
confidence: 99%
See 3 more Smart Citations
“…The virtual impedance optimization in [19] has minimized the reactive power mismatches among converters and enhanced the microgrid small-signal stability by an off-line PSO algorithm. Following the analysis of microgrid stability domain in [20], it has been suggested that the proportionalderivative reactive power controller enhances the microgrid stability margin.…”
Section: Nomenclature Abbreviationsmentioning
confidence: 99%
“…• The permissible range and optimal values for virtual impedance are affected by the microgrid load levels, this concept has not been considered in the recent researches such as [18] and [19].…”
Section: Nomenclature Abbreviationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The microgrid small-signal stability analyzed in [2] was a milestone for microgrid stability analysis. The advanced researches such as [3] optimize the virtual impedances based on small-signal stability analysis. However, the phase locked loop (PLL) as a necessary unit to control and coordinate several DGs in the MG must be taken into account, either comparing the units phases to the phase of one local DG or have a central phase reference [4].…”
Section: A Motivation and Backgroundmentioning
confidence: 99%